Fabrication of a bio-instructive scaffold conferred with a favorable microenvironment allowing for superior implant osseointegration and accelerated in situ vascularized bone regeneration via type H vessel formation - Yijun He; Wenhao Wang; Shaozhang Lin; Yixi Yang; Lizhi Song; Yihan Jing; Lihao Chen; Zaopeng He; Wei Li; Ao Xiong; Kelvin W.K. Yeung; Qi Zhao; et al. (Bioactive Materials, 2022)
The potential translation of bio-inert polymer scaffolds as bone substitutes is limited by the lack of neovascularization upon implantation and subsequently diminished ingrowth of host bone, most likely resulted from the inability to replicate appropriate endogenous crosstalk between cells. Human umbilical vein endothelial cell-derived decellularized extracellular matrix (HdECM), which contains a collection of angiocrine biomolecules, has recently been demonstrated to mediate endothelial cells(ECs) – osteoprogenitors(OPs) crosstalk. We employed the HdECM to create a PCL (polycaprolactone)/fibrin/HdECM (PFE) hybrid scaffold. We hypothesized PFE scaffold could reconstitute a bio-instructive microenvironment that reintroduces the crosstalk, resulting in vascularized bone regeneration. Following implantation in a rat femoral bone defect, the PFE scaffold demonstrated early vascular infiltration and enhanced bone regeneration by microangiography (μ-AG) and micro-computational tomography (μ-CT). Based on the immunofluorescence studies, PFE mediated the endogenous angiogenesis and osteogenesis with a substantial number of type H vessels and osteoprogenitors. In addition, superior osseointegration was observed by a direct host bone-PCL interface, which was likely attributed to the formation of type H vessels. The bio-instructive microenvironment created by our innovative PFE scaffold made possible superior osseointegration and type H vessel-related bone regeneration. It could become an alternative solution of improving the osseointegration of bone substitutes with the help of induced type H vessels, which could compensate for the inherent biological inertness of synthetic polymers.